2014
DOI: 10.1128/mcb.00349-14
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Profiling Reveals Regulatory Network Shifts and a Protective Role for Hepatocyte Nuclear Factor 4α during Colitis

Abstract: h Transcriptional regulatory mechanisms likely contribute to the etiology of inflammatory bowel disease (IBD), as genetic variants associated with the disease are disproportionately found at regulatory elements. However, the transcription factors regulating colonic inflammation are unclear. To identify these transcription factors, we mapped epigenomic changes in the colonic epithelium upon inflammation. Epigenetic marks at transcriptional regulatory elements responded dynamically to inflammation and indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 71 publications
2
50
1
Order By: Relevance
“…DSS-induced colitis results in reduced HNF4A protein levels and altered cellular localization (Chahar et al 2014); however, our results indicate the microbiota neither reduce HNF4A protein levels nor impact its nuclear localization in jejunal IECs 2 wk after colonization (Supplemental Fig. S6H,I).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…DSS-induced colitis results in reduced HNF4A protein levels and altered cellular localization (Chahar et al 2014); however, our results indicate the microbiota neither reduce HNF4A protein levels nor impact its nuclear localization in jejunal IECs 2 wk after colonization (Supplemental Fig. S6H,I).…”
Section: Discussioncontrasting
confidence: 51%
“…HNF4A has been shown to play key roles in anti-oxidative and anti-inflammatory defense mechanisms (Marcil et al 2010), so aberrant microbial suppression could promote an inflammatory state. HNF4A target genes are down-regulated in human IBD (Arijs et al 2009;Haberman et al 2014) and mouse experimental colitis (Chahar et al 2014), and the HNF4A target APOA1 has been shown to be protective against intestinal inflammation in mice (Gkouskou et al 2016). We speculate that the genes governed by this novel microbiota-HNF4A axis may include additional anti-and pro-inflammatory factors that could provide new targets for IBD therapy.…”
Section: Discussionmentioning
confidence: 99%
“… IL10RA : The IL10-receptor consists of the two subunits IL10RA and IL10RB. Sequence variants in genes encoding these two subunits are known to cause severe very early onset IBD in a monogenic fashion [32]. While the association of IL10RB with the complex form of IBD was reported by GWASs, the link with IL10RA was so far missing. SMAD5: SMAD5 is a downstream effector in BMP signaling.…”
Section: Resultsmentioning
confidence: 99%
“…4A). Wound healing was another common category, consistent with HNF4␣ playing a role in protecting the colonic epithelium from inflammatory bowel disease (10,11,13,27,78). In contrast, HNF4␣2 specifically upregulated genes involved in cell death and response to extracellular stimuli, while the only category of genes upregulated only by HNF4␣8 was cell adhesion, although several of those genes actually promote cell growth (Fig.…”
Section: Generation and Characterization Of Isoform-specific Hnf4␣-exmentioning
confidence: 98%